Tourist satisfaction with overall tour guiding experience in Taman Negara National Park, Malaysia. - Tan, Sing Ee; Abdul Aziz, Yuhanis; Awang, Khairil Wahidin; Samdin, Zaiton (CRC Press, 2012)
Tour guides provide services that enhance tourists' visiting experience. The current study aimed to determine the antecedents of tourist satisfaction with overall tour guiding experience in the context of guided tour in Taman Negara National Park. The current study is formulated on the basis of propositions that relate tour guide performance, servicescape, tour guide satisfaction with guiding service,tourist satisfaction with servicescape, tourist satisfaction with overall tour guiding experience and to observe these constructs have any influence on tourist satisfaction with overall tour guiding experience. Multiple regression analysis was employed to verify the relationships effect and revealed that tourist satisfaction with overall tour guiding experience is dependent on the antecedents of tourist satisfaction with guiding service and servicescape. The findings implicate that tour guides and servicescape are able to affect tourist satisfaction with one another's services. Further studies can be conducted to discover other antecedents that may have effect on tourists' satisfaction with overall tour guiding experience.